Work-Pattern and Postural Stress among Jhum Cultivators (IAHS Medical Journal, 2025)
Background: Agricultural workers, including jhum cultivators, frequently experienced musculoskeletal disorders and injuries as a result of the physical demands of farming.Materials and methods: A cross-sectional study was conducted to explore work patterns and assess levels of postural stress among 180 jhum cultivators in the Sreebardi Upazila of Mymensingh district, Bangladesh, from January to December 2023. Data on work patterns, postural stress, musculoskeletal issues and socio-demographic variables were collected using a semi-structured questionnaire.Results: The study included respondents aged 18 to 60 years. Among jhum cultivators, 63% reported their activities as difficult, while 14% described them as very difficult. Most participants had around 30 years of work experience and 12.8% reported having less than 10 years of experience. The majority worked between 55 to 65 hours per week, with a smaller group working fewer than 45 hours. Approximately 67% of participants mentioned that they were not involved in any other occupations. Additionally, about 73.3% of the participants adopted extremely harmful postures during their work activities, while 26.7% adopted slightly harmful postures.Conclusion: To enhance the productivity and well-being of jhum cultivators, a comprehensive strategy that integrates education, infrastructure improvements, personal hygienc, community and national-level interventions is essentialIAHS Medical Journal Vol 7(2), December 2024; 78-82